Production Of Hyaluronic Acid By Streptococcus Zooepidemicus ATCC 39920 - Shoparwe, Noor Fazliani (2010)
In view of the demand for hyaluronic acid (HA) products as a starting material for the preparation of new biocompatible and biodegradable polymers that have applications in many medical and cosmetics domains, research on microbial fermentation of HA by S. zooepidemicus ATCC 39920 was undertaken in batch and continuous system. Optimization of fermentation conditions using “one-factor-at-a-time” technique was investigated in shake-flask culture in order to determine the suitable ranges and conditions for use in the study.